Musical instruments and the paean in Archilochus - Cunha Corrêa, Paula da (2009)
El presente artículo analiza la significación de la relativamente frecuente ocurrencia de la terminología musical en los fragmentos de Arquíloco, tal como auloí y ejecutantes de auloí (fr.58.12,269), liras (fr.54.11, 93a lira + aulos), la trompeta (fr. 214) y el ejecutante de trompa (fr. 269), y la referencia al peán (fr.121) en sus contextos
This paper intends to examine the significance of the relatively frequent occurrence of musical terminology in the fragments of Archilochus, such as auloi and auloi players (fr. 58.12, 269), lyres (fr.54.11, 93a lyre + aulos), the trumpet (fr. 214) and horn player (fr. 269), and reference to a paean (fr.121), in their contexts
Keywords: Terminología musical; Peán; Arquíloco; Musical Terminology; Paean; Archilochus; Arquíloco; Poesía lírica; Análisis literario; Instrumentos musicales